First report of the causal agent of vine crown gall in Mendoza, Argentina = Primer reporte del agente causal de la agalla de corona de la vid en Mendoza, Argentina - D'innocenzo, Sandra Haydeé; Escoriaza, Maria Georgina; Diaz, Mariano Emanuel (Facultad de Ciencias Agrarias, Universidad Nacional de Cuyo, 2025)
Crown gall is one widespread grapevine disease worldwide, caused by Allorhizobium vitis (syn. Agrobacterium vitis) and Agrobacterium tumefaciens (syn. Rhizobium radiobacter). All. Vitis, is the predominant species and primary cause of the disease. This study aimed to identify and characterize molecularly the agrobacteria in plants with crown gall symptoms in Mendoza vineyards. Diseased plants with trunk-based galls were sampled from different areas of Mendoza. Two multiplex PCRs were performed for bacterial identification and characterization, demonstrating that 91.6% of the strains obtained were agrobacteria (77% A. tumefaciens and 23% All. vitis). Fifty percent of All. vitis and 16% of A. tumefaciens identified strains were pathogenic. Pathogenicity tests were also conducted on Kalanchoe daigremontiana, with resulting tumorigenic symptoms.